Effects of equine SALSA on neutrophil phagocytosis and macrophage cytokine production. - Gary Kwok Cheong Lee; Heng Kang; Janet Beeler-Marfisi; William Sears; Brandon N Lillie; Dorothee Bienzle (PLoS ONE, 2022)
Salivary scavenger and agglutinin (SALSA) is a secreted protein with various immunomodulatory roles. In humans, the protein agglutinates and inactivates microorganisms, and inhibits the release of pro-inflammatory cytokines. Saliva, which is rich in SALSA, accelerates bacterial phagocytosis, but SALSA's contribution is unclear. In horses, the functions of SALSA in inflammation remain undetermined, so they were investigated through phagocytosis and cytokine assays. Equine SALSA was purified from duodenal tissue, which contains abundant SALSA. To assess phagocytosis, fluorescently-labelled bacteria were incubated with 20, 10, 5, or 2.5 μg/mL of SALSA or phosphate buffered saline (PBS), and then incubated at 37°C or on ice with whole blood from seven healthy horses. Fluorescence was measured by gating on neutrophils using a flow cytometer, and compared between groups. To assess effects on cytokine production, alveolar macrophages were isolated from bronchoalveolar lavage fluid of five healthy horses and cultured in serum-free media for 24 hours with different concentrations of SALSA plus 1 μg/mL lipopolysaccharide (LPS), only LPS, or only media. Cytokines were measured in supernatant using an equine-specific multiplex bead immunoassay. There was significantly greater phagocytosis in samples incubated at 37°C compared to incubation on ice. Samples incubated with 20 μg/mL of SALSA at 37°C had less phagocytosis compared to samples with 10 or 2.5 μg/mL SALSA, or PBS. Alveolar macrophages incubated with SALSA plus LPS released significantly less CXC motif chemokine ligand 1, interleukin-8, interleukin-10, and tumor necrosis factor α, and more granulocyte colony stimulating factor (G-CSF), compared to macrophages incubated with LPS alone. These findings indicate anti-inflammatory effects, which may be due to interference with toll-like receptor 4 recognition of LPS or downstream signaling. Increase in G-CSF following incubation with SALSA suggests a novel mechanism for immunoregulation of alveolar macrophages by SALSA, addressing a knowledge gap regarding its functions in horses.